Optimal radiation dose to induce an abscopal effect by combining carbon-ion radiotherapy and anti-CTLA4 antibody - Liqiu Ma; Yang Li; Yoshimitsu Sakamoto; Lin Xie; Saaya Suzuki; Yukari Yoshida; Li Sui; Gang Guo; Jialing Wen; Wangcai Ren; Kazuhiro Kakimi; Kensuke Osada; et al. (Neoplasia: An International Journal for Oncology Research)
Background and purpose: Although carbon-ion radiotherapy (CIRT) has led to good outcomes, controlling metastasis is still crucial for improving overall survival. This study aimed to evaluate the effectiveness of by two combinations, one of CIRT and anti-CTLA4 antibody, the other of CIRT and anti-PD-1 antibody, applied at different radiation doses for distal tumour and metastasis suppression. Materials and methods: Murine cancer cells (colon carcinoma Colon-26 cells for experiments and osteosarcoma LM8 cells for verification) were grafted into both sides of the hind legs of syngeneic mice. Right-side tumours were irradiated with 3 Gy or 10 Gy CIRT while the left-side tumours were not irradiated, followed by the administration of the anti-CTLA4 antibody or anti-PD-1 antibody. The diameter of the tumours in both legs was measured 3 times per week after irradiation. The number of pulmonary metastases was evaluated within 3 weeks after irradiation. Results: Compared with the control group, the high-dose group showed promising anti-cancer benefits in terms of both irradiated tumours and lung metastasis, but neither 10 Gy CIRT combined with the anti-CTLA4 antibody nor 10 Gy CIRT combined with the anti-PD-1 antibody suppressed the growth of distant unirradiated tumours. In the low-dose group, the effect on primary tumour control was slightly weaker than that in the high-dose treatment group, but significant suppressive effects on both distant unirradiated tumours and metastases were observed following 3 Gy CIRT combined with anti-CTLA4 antibody treatment. Specifically, the volume of distant unirradiated tumours decreased by 40 % compared with that of the control group, and no lung metastasis was observed. Conclusion: Our findings suggest that there is an optimal dose range for the abscopal effect generated with the CIRT combined with anti-CTLA4 antibody, and it highlights a new opportunity for increased induction efficiency of the abscopal effect of combination therapy.